Device‐based prevention of neurological events in coronary artery bypass patients with calcified ascending aorta. Issue 12 (21st September 2021) - Szlapka, Michal; Peitsmeyer, Philipp; Halder, Stefanie; Natho, Oliver; Lass, Michael; Hanke, Thorsten
Abstract: Patients with severely calcified aorta undergoing conventional cardiac surgery are at increased risk for postoperative neurologic deficits. Implementation of cerebroprotective devices may substantially reduce or even eliminate the risk of the adverse neurologic events, thus enabling surgical therapy, especially when interventional treatment cannot be considered an alternative option.